Quantifying Intermolecular Interactions: Guidelines for the Molecular Recognition Toolbox - Hunter, Christopher A. (Angewandte Chemie International Edition, 2004)
Molecular recognition events in solution are affected by many different factors that have hampered the development of an understanding of intermolecular interactions at a quantitative level. Our tendency is to partition these effects into discrete phenomenological fields that are classified, named, and divorced: aromatic interactions, cation–π interactions, CHO hydrogen bonds, short strong hydrogen bonds, and hydrophobic interactions to name a few.1 To progress in the field, we need to develop an integrated quantitative appreciation of the relative magnitudes of all of the different effects that might influence the molecular recognition behavior of a given system. In an effort to navigate undergraduates through the vast and sometimes contradictory literature on the subject, I have developed an approach that treats theoretical ideas and experimental observations about intermolecular interactions in the gas phase, the solid state, and solution from a single simplistic viewpoint. The key features are outlined here, and although many of the ideas will be familiar, the aim is to provide a semiquantitative thermodynamic ranking of these effects in solution at room temperature. Noncovalent interactions are treated as a form of hydrogen bonding to produce a new universal scale that can be used to estimate the free energies of interaction between any pair of neutral functional groups in any solvent. The important parameters are provided by the molecular electrostatic potential surface (the example depicted is that for carbon tetrachloride).